Characterization and sensitivity test of the allergenic pollen proteins from Litchi Chimensis Plant - Ranajit Kumar Shaha; Nitai Roy; G.Talukdar (Universiti Malaysia Kelantan, 2013)
Pollen of Litchi chinensis (Litchi) is a major aeroallergen of Bangladesh. Pollen of this fruits plant was collected from full bloomed flower growing in different places of Rajshahi in Bangladesh. Pollen protein was extracted and partial purified by means of long-term PBS extraction, salting out, dialysis, gel filtrations and DEAE-Cellulose chromatography and the protein was designated as LFPP (Litchi flowers pollen protein). Gel filtration of the purified pollen protein gives two main peaks. The major peak gives four bands on SDS-PAGE. The enzyme (pectate lyase) proteins after gel filtration again re-purified by Ion exchange chromatography, a single band in the protein profile of LFPP, (M.W. 28kDa) was the major allergenic component of Litchi chinensis (Litchi) flower pollen. The homogeneity and the molecular weight of the protein were estimated by SDS-PAGE, and Gel filtration was 28kDa. The allergenic protein was identified by skin prick tests and showed the pectate lyase (Pel) activity. Skin-prick tests also revealed highest degree of sensitivity to the Nawabgang sample giving positive response in 80% of the patients. Skin reactivity ranged between 1+ and 3+.